Uma aplicação de opções reais no setor siderúrgico: opção de expansão. - Santos, Takeo Fugiwara (2011)
This paper will analyze the application of Real Options Analysis - ROA at an investment project at steel industry. ROA is an investment analysis model that associate the management flexibility with the traditional analysis, in this case the expansion flexibility will be used. ROA will be applied in a case study where a steel plant will be expanded from 3.0Mt/year slab capacity to 3.0Mt/year coil capacity product with higher added value. The data used in this study are the historical data from an actual production unit and the data available in the Brazilian Steel Institute - IBS. After whole analysis concluded that ROA can get a more complete result and it will be a mistake whether expansion flexibility does not been considered. The NPV would be underestimated and therefore the final decisions could be wrong.